Development of kenaf biochar in engineering and agricultural applications - Harussani, M. M.; Sapuan, S. M. (Springer, 2021)
The aim of this review is to investigate the recent development of kenaf derived biochar and its composites in various engineering and agricultural applications including nanostructure catalysts and polymer composites as kenaf biochar and activated carbon are mainly used as material adsorbents and soil amendments. A systematic review on the effect of process parameters of thermal decomposition, pyrolysis towards the production of desired biochar, therefore, is in crucial needs. Based on existing literature, the properties and production of kenaf biomass and resultant biochar are discussed in this paper. This analysis focuses on the unique characteristics of kenaf crops and the resulting biochar, which has a surprisingly large surface area and increased pore volume, to explain their prospective applications, whether in environmental utilization or engineering applications. Range of optimum surface areas for kenaf biochar are around 800–1000 m2/g where they show high adsorption properties. Whereas, the pore volume of activated carbon usually exceeds 1 cm3/g. Recent developments in engineered kenaf biochar technology and its future directions for research and development are also discussed.